2017
DOI: 10.21815/jde.016.022
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of Dental Students, Faculty, and Patients with Tooth Shade‐Matching Using a Spectrophotometer

Abstract: The aims of this study were to evaluate dental students' clinical shade-matching outcomes (from subjective use of shade guide) with an objective electronic shade-matching tool (spectrophotometer); to assess patients', students', and supervising faculty members' satisfaction with the clinical shade-matching outcomes; and to assess clinicians' support for use of the spectrophotometer to improve esthetic outcomes. A total of 103 volunteer groups, each consisting of patient, dental student, and supervising faculty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Colorimeters record tri-stimulus values and filter light in red, green and blue regions of the visible spectrum. Colorimeters are not capable of recording spectral reflectance and their accuracy can be diminished because of over usage of the filters as compared to spectrophotometers [47]. A colorimeter presents a complete measurement of light absorbed; however, a spectrophotometer quantifies the light absorbed at differing wavelengths [48].…”
Section: Colorimetersmentioning
confidence: 99%
“…Colorimeters record tri-stimulus values and filter light in red, green and blue regions of the visible spectrum. Colorimeters are not capable of recording spectral reflectance and their accuracy can be diminished because of over usage of the filters as compared to spectrophotometers [47]. A colorimeter presents a complete measurement of light absorbed; however, a spectrophotometer quantifies the light absorbed at differing wavelengths [48].…”
Section: Colorimetersmentioning
confidence: 99%
“…These results might be reasonable due to the strict protocol followed during shade selection process and the alpha score of ideal shade matching obtained by the prosthodontists evaluators. 20 stated that patient reported superior satisfaction results which may have been affected by the light shade of the restoration. Contradicting to our study results, a study by Shah et al, 2014 21 who found that the overall patient satisfaction rating were moderate and suggested that the level of patient education may have affected the final results as participants with secondary and tertiary level of education were more satisfied with the color of their final restoration compared to participants with primary level of education.…”
Section: Discussionmentioning
confidence: 99%
“…Shade detection instruments, such as colorimeters and spectrophotometers, have subsequently been introduced into dentistry. Researchers have reported equivocal outcomes when using colour-measuring devices, with some authors suggesting that these devices do not provide reliable results ( 14), and others reporting good accuracy (15).…”
Section: Discussionmentioning
confidence: 99%